Best practices for dust control in metal/nonmetal mining - Colinet, Jay; National Institute for Occupational Safety and Health. Office for Mine Safety and Health Research (Pittsburgh, PA ; Spokane, WA : Department of Health and Human Services, Centers for Disease Control and Prevention, National Institute for Occupational Safety and Health, Office of Mine Safety and Health Research, 2010)
This handbook identifies engineering controls that can assist underground and surface metal/nonmetal mining operations in reducing worker exposure to respirable silica dust.
Title from title screen (viewed on Oct. 31, 2013).
"May 2010."
Includes bibliographical references (pages 72-75).
Keywords: Mineral industries -- Dust control; Miners -- Health and hygiene; Mine dusts